Critical analysis of al-Munabbihat in hadith literature based on the context of hadith writing methods - Mohd Nor Adzhar Ibrahim; Rusni Mohamad; Mohd Solleh Ab Razak; Khairulnazrin Nasir (IDEAS, 2024)
Al-Munabbihāt is a renowned work attributed to Ibn Ḥajar al-‘Asqalānī. This study aims to analyze the credibility of attributing the book al-Munabbihāt to Ibn Ḥajar al-‘Asqalānī from the perspective of hadith writing methods. The research employs a qualitative library research method through content analysis design. The analysis specification is conducted by comparing the hadith writing methods of this book with the popular hadith book by Ibn Ḥajar al-‘Asqalānī titled Bulūgh al-Marām. The findings indicate various issues related to the hadith writing methods, such as not clarifying the highest narrator’s name, narrated with ṣīghah al-tamrīḍ, not stating the hadith sources, lacking commentary and explanation on the hadith status, and the hadith not being found in Bulūgh al-Marām despite being in the same genre. Additionally, the hadith presented are mixed with wise sayings (ḥukamā’). This clearly justifies questioning the authenticity of attributing this work to Ibn Ḥajar al-‘Asqalānī. Therefore, it is suggested that this work should no longer be attributed to him to preserve the sustainability of hadith literature, as this attribution does not reflect the esteemed reputation of Ibn Ḥajar al- ‘Asqalānī, who is revered as a great figure in the field of hadith and would undoubtedly tarnish his reputation as Amīr al-Mu’minīn fi al-Ḥadīth.